Fused Filament Fabrication of Actuating Objects. Issue 10 (25th October 2022) - Chalissery, Dilip; Schönfeld, Dennis; Walter, Mario; Ziervogel, Fabian; Pretsch, Thorsten
Abstract : Front Cover : In article 2200214, Thorsten Pretsch and co‐workers present a novel approach for two‐way four‐dimensional printing. The authors use the additive manufacturing method of fused filament fabrication to produce thermally actuating objects from a self‐synthesized polyester urethane. The introduced platform technology may facilitate the production of new generations of programmable materials.